Effect of acoustic deterrents on the behaviour of common dolphins (Delphinus delphis) - Berrow , Simon; Cosgrove , Ronan; Leeney , Ruth H.; O’Brien , Joanne; McGrath , David; Dalgard , Jeppe; Le Gall, Yves (J. Cetacean Res. Manage., 2023)
Not all delphinids are similarly affected by acoustic deterrent devices (pingers). At-sea trials were carried out to assess a range of acoustic signals and deterrents on the behaviour of common dolphins. In initial tests two acoustic deterrent devices, which previously produced an evasive response by bottlenose dolphins, failed to elicit any similar behaviour in common dolphins. A new signal output device, which permitted a range of signals to be tested at various source levels and characteristics was subsequently developed but again no significant effects on the behaviour of common dolphins were observed. Two commercially available acoustic deterrents, which had deterred common dolphins in previous studies, produced an occasional mild evasive response. Significant modification of the signal type or source level may be more effective, but our results suggest that pingers, at their current state of development, may not provide a consistently effective deterrent signal for common dolphins.